Influence of Nanoparticle CaCO3 Addition to the Physical and Mechanical Properties of Polypropylene-CaCO3 Composite - Deswita Deswita; Yusmaniar Yusmaniar; Grace Tj. Sulungbudi; Aloma Karo Karo; Sudirman Sudirman (Green Engineering Society, 2022)
Influence of Nanopaticle CaCO3 Addition to the Physical and Mechanical Properties of Polypropylene-CaCO3 Composite. This research was carried out to study the effect of adding CaCO3 nanoparticle on the physical and mechanical properties of polypropylene-CaCO3 composites. It was characterized by several parameters such as tensile strength, hardness, and thermal analysis including both melting point and heat of fusion using Differential Scanning Calorimetry (DSC). Based on XRD results, the particle size of CaCO3 after 24 hours of milling was 39 nm. There are various compositions of polypropylene-CaCO3 composites (PP MF35: nano-CaCO3) made in this study, namely 40%:60%, 35%:65%, 30%:70%, and 25%:75%. The results showed that the tensile strength of the PP MF35-CaCO3 composites decreased with increasing nano-CaCO3 content. Meanwhile, the hardness of the nanocomposites increased with increasing nano-CaCO3 content, but decreased the melting point and heat of fusions (ΔHm) of the nanocomposites. The infrared spectrum showed that the interaction between PP MF35 and nano-CaCO3 was only physical interaction and there was no chemical reaction.